2010 International Conference on Communications, Circuits and Systems (ICCCAS) 2010
DOI: 10.1109/icccas.2010.5581847
|View full text |Cite
|
Sign up to set email alerts
|

A run-time RTL debugging methodology for FPGA-based co-simulation

Abstract: Logic simulation provides SoC verification with full controllability and observability, but it suffers from very slow simulation speed for complex design. Using hardware emulation such as FPGA can have higher simulation speed. However, it is very hard to debug due to its poor visibility. FPGA-based cosimulation seems to draw a balance, but Design Under Test (OUT) still resides in FPGA and remains hard for debugging. So a run-time RTL debugging methodology for FPGA-assisted verification system is presented. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Through experimentation, it was observed that existing approaches lack internal debug capabilities that our solution can provide in order to debug video applications. In comparison with other works [18,19,24], we also provide additional capabilities. We introduce test signals within the double transceiver architecture (to encode/decode video stream) making our solution capable of analyzing a complete solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through experimentation, it was observed that existing approaches lack internal debug capabilities that our solution can provide in order to debug video applications. In comparison with other works [18,19,24], we also provide additional capabilities. We introduce test signals within the double transceiver architecture (to encode/decode video stream) making our solution capable of analyzing a complete solution.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach to tackle this problem is proposed in [19]. The verification method compiles the test-bench on a computer.…”
Section: Background and Related Workmentioning
confidence: 99%
“…It took 55.81 s to monitor the entire validation at a minimum amount of BRAMs and it generated a VCD file with a size of 434 MB. In future works, this monitoring implementation can be improved with a scan-chain methodology presented in [20] or statistical sampling method [21].…”
Section: Resultsmentioning
confidence: 99%
“…Our system expects this specification only at block level, which is much easier owing to a designer's block level view of a SoC design. Co-simulation based RTL debug systems have been studied in [11,12]. In both cases, testbench resides on HDL simulator and the DUT runs on FPGA based emulator, while observability of internal nodes of DUT is provided via interface calls of HDL simulator.…”
Section: Previous Workmentioning
confidence: 99%
“…In both cases, testbench resides on HDL simulator and the DUT runs on FPGA based emulator, while observability of internal nodes of DUT is provided via interface calls of HDL simulator. In [11], internal node probing in FPGA is achieved by connecting DUT signals to a PCI-extended bus, and in [12] the same is achieved by insertion of scan chains in design. Both the systems have substantial area overhead that reduces effective capacity of the emulator.…”
Section: Previous Workmentioning
confidence: 99%